Morphology of organomineral formations of kidneys of Dnipropetrovsk region residents - Ishkov, V. V.; Kozii, Ye. S. (ІГТМ НАН України, 2021)
The article presents the results of morphology research of the organomineral formations of the residents of Dnipropetrovsk region and proposes the typification of uroliths according to the peculiarities of their morphology.

В статті наведено результати досліджень морфології органомінеральних утворень мешканців Дніпропетровщини й запропонована типізація уролітів за особливостями їх морфології.

В статье результаты исследований морфологии органоминеральных образований жителей Днепропетровщины и предложена типизация уролитов по особенностям их морфологии.
Морфологія органомінеральних утворень нирок мешканців Дніпропетровщини
Keywords: organomineral formations; uroliths; morphology; crystals; concretions; urolithiasis; органомінеральні утворення; уроліти; морфологія; кристали; конкременти; сечокам’яна хвороба; органоминеральные образования; уролиты; морфология; кристаллы; конкременты; мочекаменная болезнь